O enigma saussuriano do ponto de vista-objeto - Marques, Allana Cristina Moreira (2021)
On this thesis, we have the assumption that in Linguistics the point of view creates the object. This affirmation, well known in the realm of modern linguistic studies, was sustained the first time in the posthumous edition of the Course of General Linguistics (CGL), in 1916, and for this reason it is attributed to Ferdinand de Saussure. In his work, recognized as the turning point for the foundation of Modern Linguistics, the saussurian affirmation was in the spotlight. On chapter “Object of Linguistics”, it appears as an epistemological solution to the problem concerning the integral and concrete object of Linguistics. It is from the comprehension that the objects are not given beforehand in Linguistics that Saussure sustains that the point of view creates the object. This outrageous proposition, as Normand (2009[2000]) says, was not ignored by those who read Saussure. And many scholars have reported some misunderstandings about it as well as the effacing of the concept of point of view in CGL. Because of this way of reading Saussure, the saussurian proposition was taken by the means of what we call the outrage-effacing. However, by studying Saussure’s manuscripts, we discover another way of reading his work: the one that creates the proposition that the point of view creates the object by the means of the outrage-scattering, what we sustain on this thesis. We do so because we the think the point of view, even though it is in the spotlight in CGL, is scattered in his further considerations, mainly when concerning the concept of relation, essential to understanding language as a system of signs. Therefore, for sustaining our proposition, we study two saussurian manuscripts: Notes pour un livre sur la linguistique générale 10f., which contains what we call the enigma of the point of view, and De l’essence double du langage, which was discovered in 1996 and makes part of the same project as the first manuscript, according to Engler (1997). Besides, we read some notebooks of Saussure’s students, which contain the content taught by Saussure in Geneva during his courses, in order to show how Saussure treated the concept of point of view in his classes. In the end, we discuss details concerning the relation between the editing of CGL and how the point of view is presented in it, and we present another way of reading CGL. This is what we call the disarmed eyeshot, which means we read Saussure without the help of critics in order to show how the point the view is treated by Saussure himself in CGL.